Trends and needs in requirements engineering research in Ibero-America: insights from a panel - Vara, Jose Luis (2019)
Some aspects characterise Requirements Engineering (RE) research from different regions, whereas others constrain RE and RE approaches should not disregard them. Within this context, this paper aims to provide new insights into the trends and needs in RE research in Ibero-America. We have analysed the results from a panel at WER 2015 on the characteristics in Ibero-America that RE research should consider, the topics uccessfully researched in the region, the topics not sufficiently researched, and the topics on which future research should focus. Among the conclusions, Ibero-America seems to have specific social and cultural characteristics that impact RE, research on goaloriented RE and RE for web-based systems can be regarded as successful, how to improve requirements quality should have been further studied, and RE education and knowledge transfer must be addressed in the future.